Determinants of substance use among adolescents aged 10-19 years in Tanga Region, Eastern Tanzania: A cross-sectional analysis. - Sanun Ally Kessy; Innocent B Mboya; Shraddha Bajaria; Innocent Yusufu; Mashavu H Yussuf; Amani Tinkasimile; Frank Mapendo; Wilbald Anthony; Imani Irema; Isaac Willey Lyatuu; David Sando; Azan Nyundo; et al. (PLOS Global Public Health)
Background Despite adolescents making up a significant part of the global population, they have high rates of substance use, linked to various health problems and risky behaviours and increased risk of negative social, cognitive, and physical consequences. Studies on substance use and related risk behaviours among adolescents in Tanzania are crucial for informing targeted interventions and policies to safeguard the health and development of this vulnerable population. We aimed to assess the prevalence and determinants of substance use among adolescents in the Tanga region, eastern in Tanzania. Methods We conducted a secondary analysis of cross-sectional survey data among 1,262 in-school (n = 1,031) and out-of-school (n = 231) adolescents conducted in Tanga, Tanzania in 2021. Data was collected using the Global School Health Survey (GSHS) questionnaire that included questions on substance use, specifically alcohol, smoking marijuana and tobacco, and recreational drugs like cocaine and heroin. Modified Poisson regression models estimated the factors influencing lifetime and current (within the past 30 days preceding the survey) substance use using Stata software version 17. Results Among 1,262 adolescents, the lifetime and current prevalence of substance use were 8.6% and 3.2%, respectively (4.1% and 0.8% among in-school vs. 29% and 13.9% among out-of-school adolescents). The most reported substance used over a lifetime among both in-school and out-of-school adolescents was smoking (2.3% and 27.7%), followed by alcohol drinking (2% and 10.4%). A higher likelihood of lifetime and current substance use was found among older adolescents (15-19 years), males, and who owned a mobile phone, with a social media account, with history of sexual activity, and out-of-school adolescents. Conclusion Substance use is common among the adolescent population in eastern Tanzania. Policies to keep adolescents in school are instrumental in reducing risk behaviours during adolescence. Targeted behaviour change interventions should be considered for older adolescents (15-19 years), out-of-school, males, and those exposed to sexual activities.